Analisis Komunikasi Karyawan Food & Beverage Service Di Sudamala Resort Komodo Labuan Bajo - Elisabeth Hanggu; Elenora Ngahum (Pusat Penelitian dan Pengabdian Politeknik eLBajo Commodus, 2024)
Abstract When it comes to determining guest happiness, effective communication becomes crucial. In pre-trial conversations at Wae Rebo Restaurants, Sudamala Komodo Labuan Bajo, miscommunication happens frequently. The study outlines the reasons behind misunderstandings and identifies successful communication techniques that pre-trials should employ. This sort of research is qualitative-descriptive, with data gathered through observations and interviews. The veracity of the data is checked using a triangulation of theory and data. The study's findings revealed that mechanical disruptions, semantic distortions, speaker and counterpart motivation, interests, and prejudices all contribute to pre-examination malcommunication. The conveyed communication approach is Prioritizing the visitor or coworker while conversing is the first duty of the waiter or server. Notes can be used to confirm what the speaker is saying is not forgotten. Secondly, improve your understanding of both your mother tongue (Indonesian) and foreign languages (English, Mandarin, and others) so that it can help the communication process when serving foreign guests. Third, understand the team workflow, job desk, and communication patterns that apply in the workplace without having to be reminded repeatedly by the boss or supervisor. Keywords: communication barriers, waiters, food and beverage service, restaurant.